Spatial distribution of low birthweight infants in Taubaté, São Paulo, Brazil - Luiz Fernando C. Nascimento; Thais Moreira Costa; Maria Stella A. da C. Zöllner (Sociedade de Pediatria de São Paulo, 2013)
OBJECTIVE: To identify the spatial pattern of low birth weight infants in the city of Taubaté, São Paulo, Southeast Brazil. METHODS: Ecological and exploratory study, developed with the data acquired from the Health Department of Taubaté, regarding the period from January 1st 2006 and December 31st 2010. Birth certificates were used to obtain the data from infants weighing less than 2500g. A digital basis of census tracts was applied and the Global Moran index (IM) was estimated. Thematic maps were built for the distribution of low birth weight, health centers and tracts, according to the priority care (Moran map). The adopted statistical significance was α=5% and TerraView software conducted the spatial analysis. RESULTS: There were 18,915 live births during the study period, with 1,817 low birth weight infants (9.6%). The low birth weight infants' prevalence during the period ranged from 9.3 to 9.8%. A total of 1,185 infants with known addresses, compatible with the digital base (65.2% of low birth weight infants), were included. The IM for low birth weight was 0.12, with p<0.01; regarding the health centers distribution, IM was -0.07, with p=0.01. The Moran map identified 11 census tracts with high priority for intervention by health managers, located in the outskirts of the city. CONCLUSIONS: The spatial analysis identified the low birth weight distribution by census tracts and the sectors with a high priority for intervention.